CNJ e judicialização: o reconhecimento do poder de atuação do CNJ pelo STF e suas consequências na judicialização - Jimenez, Priscilla da Costa Lima (2014)
The subject of this paper is due to the concern about the recognition of and respect to the power of the National Justice Council (Conselho Nacional de Justiça CNJ), be it as the administrative-strategic, budgetary-financial and disciplinary controller of the Judicial power; be it as the responsible for the progression and development of Justice in society. Being this study an exploratory research, the author sought to develop a broad empirical study in order to give rise to theoretical studies on the matter. To that extent, aiming at understanding the dynamics of recognition and respect to the powers of CNJ by the Judicial power and by the society and at measuring the impact of the creation of the CNJ in the number of lawsuits that discuss those before the Supreme Court (Supremo Tribunal Federal STF), the author has decided to research the lawsuits in which the STF acknowledged the powers of the CNJ in the first place and afterwards, research (i) the lawsuits that challenge these powers even after their recognition and try to measure the continuity or not of the respect to these powers; and (ii) the lawsuits that challenge these powers before their recognition by the STF, in order to enable the discussion around the judicial costs and benefits of the recognition of the powers of the CNJ